Assessment of utility values and QALYs after primary PCI with DP-Xience and BP-Biomatrix stents. - Salma Bibi (Public Library of Science (PLoS), 2021)
Background Primary percutaneous coronary intervention (PPCI) is the recommended treatment in ST elevated myocardial infarction (STEMI). The determination of Quality of life (QoL) for various options of coronary revascularization is important for establishment of a comprehensive care plan. Studies of QoL in interventional cardiology are scarce. Our study has compared utility scores and quality adjusted life year (QALY) of 2nd and 3rd generation drug eluting stents (DES). Methods An observational cohort study was conducted to evaluate QoL and QALY using EQ-5D-5L questionnaire. Patients undergoing PPCI between July-Dec 2019 were evaluated after completion of one year of procedure. Results Total 334 patients were evaluated, study population consisted of a greater number of males (87.13%) than females. Mean utility value was more in 3rd G Biomatrix stents; 0.829 ± 0.11 than 2nd G Xience stents; 0.794 ± 0.11 (p < 0.05). Visual analogue scale (VAS) value was also high in 3rd G DES (81.84 ± 8.29) as compared to 2nd G DES (77.81 ± 9.01); p< 0.05. A significant association was found between utility scores/VAS and age, DM, HTN, Current smoking, family history and CAD diagnosis. There was a gain of 0.035 QALY with the use of Biomatrix DES. Conclusion Health related quality of life (HRQOL) is a leading support in the decision making of therapeutic interventions. Our study has found that Biodegradable polymer (BP) Biomatrix DES are superior to the Durable polymer (DP) Xience DES having better QoL and QALY.